2020
DOI: 10.1016/j.celrep.2020.107526
|View full text |Cite
|
Sign up to set email alerts
|

Wdr47 Controls Neuronal Polarization through the Camsap Family Microtubule Minus-End-Binding Proteins

Abstract: Highlights d Wdr47 ensures proper neuronal polarity both in vivo and in vitro d Wdr47 controls neuronal polarity by modulating regional microtubule dynamics d Wdr47 functions in unpolarized neurons through Camsap family proteins d The neuronal function of Wdr47 is required for neonatal mouse survival

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
69
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(80 citation statements)
references
References 65 publications
9
69
1
Order By: Relevance
“…concentrated Camsaps into the central lumen, where Camsaps stabilized the minus ends of the seeds to allow central MT elongation. As emerging evidence suggests that Wdr47, Camsaps, and Katanin also similarly impact neuronal polarization and axonal growth 14,15,17,40,41 , our findings indicate that the same pathway is used to properly generate and organize non-centrosomal MT arrays in polarized subcellular compartments such as the axon and motile cilium.…”
Section: Introductionsupporting
confidence: 60%
See 4 more Smart Citations
“…concentrated Camsaps into the central lumen, where Camsaps stabilized the minus ends of the seeds to allow central MT elongation. As emerging evidence suggests that Wdr47, Camsaps, and Katanin also similarly impact neuronal polarization and axonal growth 14,15,17,40,41 , our findings indicate that the same pathway is used to properly generate and organize non-centrosomal MT arrays in polarized subcellular compartments such as the axon and motile cilium.…”
Section: Introductionsupporting
confidence: 60%
“…In this study, we demonstrated that three groups of interacting proteins, the WD40 repeat-containing Wdr47 (also called Nemitin) 14,36 , Camsaps, and the MT-servering enzyme Katanin 12,[37][38][39] , co-operated to achieve the initial central MT formation in mammalian multicilia. Katanin produces central MT seeds by severing the peripheral MTs.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations